PENGATURAN HUKUM INDONESIA TENTANG PEMANFAATAN LINGKUNGAN UNTUK KESEJAHTERAAN RAKYAT - Dahwir, Ali; Barhamudin, Barhamudin (Solusi, 2020)
One of the failures of countries in the world, including Indonesia in actualizing sustainable development is the inability of policy makers to integrate the three pillars of sustainable development (ecological, economic, social, cultural) and third pillars with good governance into decision-making processes of the country. As a result of a policy often can not dispel the environmental damages. Environmental quality and declining threatens the continuity of life of humans and other living creatures, as well as increasing global warming resulting in climate change and this will exacerbate environmental degradation. It is necessary for the protection and management of the environment seriously and consistently by all stakeholders. Law is an instrument of social control, and a means of social change or the means of development, the rule of law is necessary to prevent and mitigate the negative impacts of development.